THE IMPACT OF SPOTIFY ON EFL LISTENING COMPREHENSION - Sari, Meina Nurfika; Indriani, Lilia; Safiroh, Sindi Dian (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2023)
The aim of this study is to investigate the impact of Spotify on EFL Listening comprehension. Spotify is an application for listening to English songs to determine what words the singer said and the song's meaning. The researcher uses a qualitative research design—the data taken from questionnaire to fifth-semester English Department Students in University through google form. The objectives are: (1) to investigate the impact of EFL listening comprehensions through Spotify. According to the findings, Spotify has a significant effect on EFL students' listening comprehension. Furthermore, the questionnaire results revealed that students have a favourable attitude toward the use of Spotify in listening exercises. Spotify, according to participants, provided active learning, exciting activities such as listening to music with lyrics and also meaningful podcasts, which made them feel more motivated to learn English. This study suggested that teachers use Spotify to teach listening because of its effectiveness as a technology-based learning tool.